11.9k views
3 votes
-2x + 3y = -12 2x + y = 4 after adding the two equations to eliminate x you are left with 4y = -8 solve for y: y = -2 Substituting y = -2 back into the first equation gives: -2x + -6 = -12 Solve for x. what is the solution to the system for equations? (___, ___)

-2x + 3y = -12 2x + y = 4 after adding the two equations to eliminate x you are left-example-1

1 Answer

5 votes

\begin{gathered} -2x+3y=-12 \\ 2x+y=4 \\ \text{adding the equations} \\ -2x+2x=0 \\ 3y+y=4y \\ -12+4=-8 \\ 4y=-8 \\ y=-(8)/(4)=-2 \\ \text{substitute y=-2 in equation 1} \\ -2x+3(-2)=-12 \\ -2x-6=-12 \\ -2x=-12+6 \\ -2x=-6 \\ x=(-6)/(-2) \\ x=3 \end{gathered}

User Gabe Durazo
by
5.1k points